2018
DOI: 10.1155/2018/2751250
|View full text |Cite
|
Sign up to set email alerts
|

Differential Relationship between Intermuscular Adipose Depots with Indices of Cardiometabolic Health

Abstract: Background Globally, accumulation of intermuscular adipose tissue (IMAT) is positively associated with insulin resistance. Whether this association is observed consistently in different skeletal muscles and encompasses other markers of cardiometabolic health is not well known. Objectives The purpose of this secondary analysis study was to investigate associations among thigh or calf IMAT stores and indices of cardiometabolic health in adults who are overweight and obese participating in dietary interventions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 52 publications
2
17
0
Order By: Relevance
“…Each one-standard deviation increase in IMAT (~6.8% greater IMAT) is associated with a 40% greater mortality risk over a 10-year period 7 . IMAT volume is higher in individuals with obesity and type 2 diabetes 8,9 and is associated with high levels of inflammation, insulin resistance, obesity, sarcopenia, and lower physical performance in adults and the elderly population 10,11 . Recently, Bergia et al showed that greater IMAT in the thigh is a better predictor of cardiometabolic risk than greater IMAT in the calf in adults who are overweight and obese 11 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Each one-standard deviation increase in IMAT (~6.8% greater IMAT) is associated with a 40% greater mortality risk over a 10-year period 7 . IMAT volume is higher in individuals with obesity and type 2 diabetes 8,9 and is associated with high levels of inflammation, insulin resistance, obesity, sarcopenia, and lower physical performance in adults and the elderly population 10,11 . Recently, Bergia et al showed that greater IMAT in the thigh is a better predictor of cardiometabolic risk than greater IMAT in the calf in adults who are overweight and obese 11 .…”
mentioning
confidence: 99%
“…IMAT volume is higher in individuals with obesity and type 2 diabetes 8,9 and is associated with high levels of inflammation, insulin resistance, obesity, sarcopenia, and lower physical performance in adults and the elderly population 10,11 . Recently, Bergia et al showed that greater IMAT in the thigh is a better predictor of cardiometabolic risk than greater IMAT in the calf in adults who are overweight and obese 11 . Interestingly, IMAT is a unique ectopic adipose depot involved in a range of adverse health outcomes similar to VAT 12 .…”
mentioning
confidence: 99%
“…In contrast, our study found no associations between lower thigh IMAT radiodensities and fasting glucose but did find significant associations with higher insulin and insulin resistance, even after adjustment for VAT radiodensities. It is important to note that regional IMAT accumulation may differentially impact the relationship between IMAT and metabolic health . Comparisons of regional distribution of IMAT are not well studied; however, results from Ruan et al suggest that the thigh may have a greater amount of IMAT compared with the waist.…”
Section: Discussionmentioning
confidence: 99%
“…Statistical significance was based on α = 0.05, and analyses were performed using SAS software version 9.4 (SAS Institute, Inc., Cary, North Carolina). A graphical three‐dimensional scatterplot was generated using the package “scatterplot3d” in R version 3.5.2 (R Foundation for Statistical Computing, Vienna, Austria).…”
Section: Methodsmentioning
confidence: 99%
“…Whole body lean (non-bone soft tissue) and fat tissue masses were measured by dual-energy X-ray absorptiometry (DXA, GE Lunar Prodigy with version 11.1 enCORE iDXA software, Madison, WI) during baseline week 3 and intervention week 16. Right mid-thigh and mid-calf cross-sectional areas, muscle areas, subcutaneous fat areas, and intramuscular adipose tissue (IMAT) areas were measured using magnetic resonance imaging (MRI, 3T General Electric Signa HDx system), as described [23]. Abdominal MRIs at the L3-L4 vertebral disc were also taken due to high correlations with whole abdominal visceral adipose tissue (VAT) volume [24].…”
Section: Body Compositionmentioning
confidence: 99%